The Effect Business Risk, Profitability and Liquidity on Capital Structure In Mining Companies In The Coal Sub-Sector Listed On The Indonesia Stock Exchange In 2019 - 2022 - Frasetio, Hari; Halim, Edyanus Herman; Fitri (International Journal of Economic, Business & Applications, 2024)
This study aims to determine the influence of business risk, profitability and liquidity on capital structure in Mining Sector companies in the Coal sub-sector listed on the Indonesia Stock Exchange in 2019-2022. The population in this study is 29 companies in the Mining Sector of the Coal Sub-Sector Listed on the Indonesia Stock Exchange in 2019-2022. Sample selection was carried out based on the purposive sampling method. So that the sample in this study is 22 companies. Multiple linear regression analysis is used to analyze the relationships between variables. The results show that the degree of operating leverage does not have a significant effect on the Debt to Equity Ratio. Return On Equity has a significant negative effect on the Debt to Equity Ratio. The Current Ratio has a significant negative effect on the Debt to Equity Ratio.